General geology and geomorphological processes of Panggung Lalat, Gua Musang - Siti Nur Hidayah Ahmad (2018)
The geological mapping is carried out at Panggung lalat which is a part of district of Gua Musang, Kelantan in order to collect the data of rock distribution, structural geology, stratigraphy and geomorphology. The rock samples were collected to laboratory work by doing thin section for petrography analysis in order for identiﬁcation of rock types. The objectives of the research are to produce the geological map with a scale 125,000 using the Geographical Information System (GIS) and to identify the geomorphological process of Panggung Lalat, Gua Musang particularly hillslopes geomorphology, weathering, landform that involved. There are two methods that involved in the research which are geological and geomorphological mapping. Final results showed the rock distribution of the study area is granite which are coarser grain and medium grain, limestone, tuff, and shale. The limestone and interbedded of tuff, and shale is under Gua Musang Formation which in Middle Permian to Upper Triassic. The geomorphology of the area is hillslopes landform. Geology structure observed from ﬁeld site was quartz vein, calcite vein, fractures, bedding, and xenolith. The depositional environment of the study area can assume as shallow marine environment. From the geomorphological sampling form the geomorphological processes particularly involved in hillslopes geomorphology, weathering and landform. Based on ﬁeld observations there are three different of localities in study area shows as hillslopes morphology. Final result the hillslopes geomorphology processes included three types leaching, soil creep and rainsplash and sheet wash. The weathering processes include in study area is physical, chemical, and biological. The climate and human activities affected the rate of weathering in study area. Moisture and temperature were factor for strength of the rock decrease. From DEM data, the slope gradient map produced to shows as the slopes system that classiﬁed as steepness area.